2012
DOI: 10.2139/ssrn.2028725
|View full text |Cite
|
Sign up to set email alerts
|

Do Reticent Managers Lie During Firm Surveys?

Abstract: Previous studies have shown that reticent managers, who are identified through a series of random-response questions, answer questions about corruption, firm performance and how honest they are differently from other managers. If reticent managers' answers are different because they are lying, estimates of these behaviors will be inaccurate. But it is also possible that reticent managers answer questions differently because they and their firms are different. This paper presents evidence consistent with the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Many previous papers have shown that this is the case. People who ignore the instructions to the random response questions also appear to misreport other information from non-random response questions (Azfar & Murrell, 2009;Clarke, 2011Clarke, , 2012Clausen et al, 2012;Friesenbichler et al, 2014;Jensen & Rahman, 2011).…”
Section: Identifying Answer Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous papers have shown that this is the case. People who ignore the instructions to the random response questions also appear to misreport other information from non-random response questions (Azfar & Murrell, 2009;Clarke, 2011Clarke, , 2012Clausen et al, 2012;Friesenbichler et al, 2014;Jensen & Rahman, 2011).…”
Section: Identifying Answer Biasmentioning
confidence: 99%
“…We use it in a different way, originally proposed by Azfar and Murrell (2009), to identify respondents who do not answer sensitive questions truthfully. Previous studies have shown that answer bias affects sensitive questions, particularly referring to corruption and performance (Azfar & Murrell, 2009; Clarke, 2011, 2012; Clarke, Friesenbichler, & Wong, 2015; Clausen, Fagerberg, & Gulbrandsen, 2012; Friesenbichler, Clarke, & Wong, 2014; Jensen & Rahman, 2011). We further discuss the method in greater detail.…”
Section: The Present Studymentioning
confidence: 99%
“…4 Randomization methods other than CM are increasingly used in surveys among firms in developing countries to study topics which are unrelated to tax evasion. Azfar and Murrell (2009), Clarke (2011, 2012a, Clausen et al (2011) andJensen andRahman (2011) for instance apply various versions of these methods to identify respondents who give knowingly false answers to questions about corruption and firm performance. In addition, Karlan and Zinman (2012) examine self-reported information about the use of loan proceeds by clients of microfinance institutions.…”
Section: Introductionmentioning
confidence: 99%
“…The research community also knows that reticent managers respond differently to non-reticent managers when asked non-sensitive survey questions. For example, evidence has been found for reticent managers reporting that they pay their workers higher wages, whilst in reality paying wages no higher than their competitors (Clarke, 2012); also, reticent managers are more likely to answer questions on corruption but less likely to report corruption (Clarke, Friesenbichler, & Wong, 2015). This article investigates the reasons for underreporting of sensitive acts by firms, even when those same firms have protection against being found guilty of those acts.…”
Section: Introductionmentioning
confidence: 99%